The Role of Gontor Educational Values in Shaping The Morals of Santri as A Provision for Realizing A Civil Society - Purwati, Dwi; Haryanto, Sigit (Universitas Muhammadiyah Surakarta, 2025)
This study aims to describe and analyze how the value-based education system applied at Pondok Modern Darussalam Gontor contributes to the moral formation of students (santri), and how these morals serve as a foundation for building a civil society. It also seeks to explore strategies of value education that are adaptive to modern challenges while remaining rooted in Islamic principles. The research employed a descriptive qualitative method, utilizing in-depth interviews, participatory observation, and documentation. The informants included the boarding school leaders, senior teachers, senior students, and alumni. The findings indicate that core values such as sincerity, simplicity, self-reliance, Islamic brotherhood, and responsible freedom are effectively internalized through daily habituation, role modeling, and a highly educational environment. These values shape the students into honest, disciplined, socially responsible individuals with strong empathy and leadership skills. The resulting character becomes essential social capital for building a civil society that is ethical, tolerant, just, and civilized. Furthermore, Gontor’s educational strategy has proven to be adaptive to globalization and technological advancement while maintaining a firm commitment to Islamic values. The study concludes that Gontor’s educational system not only forms pious individuals but also prepares its students to become transformative agents in society.